PENERAPAN POLA PBMP DAN MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN KETUNTASAN BELAJAR PADA MATERI KIMIA KARBON SISWA KELAS XII-IPA-2 SMAN 6 MADIUN SEMESTER 2 TAHUN PELAJARAN 2014-2015 - Tintin Dwi Sumarni (IKIP PGRI MADIUN, 2016)
This study aims to determine the participation and motivation of the students, student learning outcomes and determine the quality of chemistry by combining Jigsaw model and PBMP patterns on the material of Carbon Chemistry. This study is a Classroom Action Research held on two cycles. The subjects of this study were the students of class XII-IPA-2 SMAN 6 Madiun in the Academic Year 2014-2015. The research design uses Classroom Action Research with two cycles, where each round consists of plans, activities and observation, reflection and revision of the draft. The methods of data collection is test data results, student activity sheets observation and data management of learning. While the devices used are the Lesson Plan, Hand Out, and the Student Worksheet. Data were analyzed descriptively. The results achieved in this study are: 1) The score of each test cycle shows that the application of a PBMP and Jigsaw model can improve students' mastery learning. In the first cycle, the percentage of classical completeness is 70.59%. In the second cycle, the percentage of classical completeness is 85.29%. 2) The response of students in applying PBMP patterns and Jigsaw model in the learning process carbon chemistry provides positive feedback. It can be seen from the responses of students that they are more motivated with Jigsaw and PBMP with a percentage of 70.6%. Learning management increased from the first cycle to the second cycle. Positive activities undertaken students also increased from the first cycle to the second cycle.